Conversational Implicature and Politeness Principles in Sumbawanese Daily Conversations - Pebriantika, Erlin (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2017)
This study investigated convesational implicatures and politeness principles in Sumbawanese daily conversations. This study concerned on examining several forms of violation in each maxim of Cooperative Principle and Politeness Principle. It also examined the importance reasons from native speakers of Samawa language, particularly Taliwang dialect in applying implicatures for their daily communications. This research employed descriptive qualitative method. The purposive sampling had been applied to take samples toward this study. Conversational Analysis was used to analyze the data. Data were collected by using the recording of Sumbawanese daily conversations, dialects of Taliwang. Based on the results of the study, it was found that a violation had emerged from each of Cooperative Principle‟s maxims and Politeness Principle‟s maxims in single and double forms. All forms of violations in a single maxim emerged from both of Cooperative Principle‟s maxim and Politeness Principle maxim. Violations in the form of a double maxim of the Cooperative Principle were divided into six types, covering; 1) Quantity and Relevance, 2) Manner and Relevance, 3) Quality and Manner, 4) Quantity and Manner, 5) Quality and Quantity, and 6) Quality and Relevance. While, in double maxim of Politeness Principle, the violations included five forms, namely; 1) Tact and Agreement, 2) Tact and Approbation, 3) Sympathy and Tact, 4) Generosity and Modesty, and 5) Sympathy and Approbation. Furthermore, the general reasons of applying implicatures in native speaker‟s daily conversations were for transferring information to the addressee, changing topic of conversation, maintaining politeness of the utterance, hiding something from the addressee, refusing something, asking for something and getting something out of the addressee. This research was also expected to contribute more to Samawa language‟s learning materials in particular and to the relation between language and society in any language in common.